GERAKAN ECOVILLAGE BERBASIS SABILULUNGAN KONSERVASI LAHAN GREENBELT WADUK JATIGEDE - Purnama Putra; Puput Putrianika; Siti Nurhidayah; Hasan Basri; Ridwan Ridwan; Dian Desty Widyowati (LPPM Universitas Islam 45 Bekasi, 2022)
Jatigede Reservoir is the second largest reservoir in Indonesia. Jatigede Reservoir also has the main function for irrigation facilities and hydroelectric power (PLTA). In addition, it also functions as a means of freshwater aquaculture, water sports facilities, recreational facilities, and so on. The construction of the Jatigede Reservoir provides great benefits, but on the other hand there are sacrifices for several interests, namely the loss of community land, changes in community livelihoods and the continuity of the reservoir related to the reservoir area border with the community. Ecosystem conservation to strengthen the sustainability of the reservoir requires the concept of sabilulungan which is the local wisdom of the Sundanese people who live around the reservoir. The value of sabilulungan is not only at the level of mutual cooperation but also closely related to its relationships and interactions with others, the environment and with God. This Community Service uses the concept of Socialization and Participatory in the Sabilulungan-based Ecovillage theme in forming and maintaining the Jatigede reservoir greenbelt so that it can have an impact on social, economic, ecosystem and natural conservation aspects. The activities carried out were in the form of counseling related to the sabilulungan-based ecovillage concept, planting community forest plant seeds, health checks and distribution of basic food packages to the Cibugel village community. This activity involves village officials, community leaders, RT and RT heads, hamlet heads and other community members, in addition to expanding the scope and strengthening the level of success of the Community Service team program in collaboration with PT Migas Hulu Jabar. Community participation with village officials and community leaders is the most important thing in the sabilulungan-based Ecovillage concept, academics and CSR managers are other complementary stakeholders in maintaining the program consistency.